Nitinol Modified by In Situ Generated Diazonium Salts as Adhesion Promoters for Photopolymerized Pyrrole. Issue 42 (12th November 2018) - Jacques, Amory; Saad, Ali; Chehimi, Mohamed M.; Poleunis, Claude; Delcorte, Arnaud; Delhalle, Joseph; Mekhalif, Zineb
Abstract: There is a growing demand for biomaterials, however their interaction with living tissues requires their modification by protective and biocompatible coatings. In this context, the present work investigates the electrografting of in situ generated aminophenyl diazonium (PD‐NH2 ) on Nitinol (NiTi). The PD‐NH2 grafting protects the TiO2 surface layer of NiTi and enhances the blocking properties towards Ru(NH3 )6 Cl3 used as redox probe. Hypotheses on the interfacial bond between NiTi and the grafted PD‐NH2 layer are proposed. Post‐modification is performed by photopolymerization of pyrrole using electrografted PD‐NH2 and PD−Py (4‐pyrrolyphenyldiazonium) as adhesion promoters. These NiTi surface treatments lead to the formation of well adherent silver‐polypyrrole (PPy−Ag) nanocomposite films. Abstract : Nitinol (NiTi) samples were electrografted with diazonium salts to provide surface anchored aminophenyl and 4‐pyrrolylphenyl groups and further coated with polypyrrole‐silver nanocomposite coatings by photopolymerization of pyrrole. Aryl groups constitute ultrathin barrier layers to redox probes as well as excellent excellent adhesion promoters to the polypyrrole‐silver coatings. In contrast, adhesion failure was noted for the composite coating‐untreated NiTi interface.